2021
DOI: 10.1021/acs.jpcb.1c05225
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Ag3PO4/Polypropylene Composites for Inactivation of SARS-CoV-2 and Other Important Public Health Pathogens

Abstract: The current unprecedented coronavirus pandemic (COVID-19) is increasingly demanding advanced materials and new technologies to protect us and inactivate SARS-CoV-2. In this research work, we report the manufacture of Ag 3 PO 4 (AP)/polypropylene (PP) composites using a simple method and also reveal their long-term anti-SARS-CoV-2 activity. This composite shows superior antibacterial (against Staphylococcus aureus and Escherichia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…The observed dependence of the stability of SARS-CoV-2 on different materials , suggests that materials can be specifically developed to reduce the lifetime of SARS-CoV-2 on solids. Coatings are particularly attractive because they can be applied to a variety of different objects with a low amount of active material, and this idea has stimulated the fabrication of antiviral coatings. To date, surface coatings of copper , and its two oxide forms, , silver oxide, zinc oxide, and light-activated titanium dioxide have shown promising results for practical application on common touch surfaces with a high frequency of contacts. Moreover, silver , and zinc species , have also accelerated the inactivation of this virus.…”
Section: Introductionmentioning
confidence: 99%
“…The observed dependence of the stability of SARS-CoV-2 on different materials , suggests that materials can be specifically developed to reduce the lifetime of SARS-CoV-2 on solids. Coatings are particularly attractive because they can be applied to a variety of different objects with a low amount of active material, and this idea has stimulated the fabrication of antiviral coatings. To date, surface coatings of copper , and its two oxide forms, , silver oxide, zinc oxide, and light-activated titanium dioxide have shown promising results for practical application on common touch surfaces with a high frequency of contacts. Moreover, silver , and zinc species , have also accelerated the inactivation of this virus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this material proved to be particularly effective against the pathogenic microorganisms tested, without causing any type of dermatitis to its user. In other works, we were able to immobilize SiO 2 -Ag particles in different polymers, reaching over 99% viral clearance in just 15 min. , Very recently, we reported that the incorporation of Ag 3 PO 4 into a polymer matrix leads to a composite with antimicrobial action against SARS-CoV-2 and other opportunistic and potential pathogens …”
Section: Introductionmentioning
confidence: 78%
“…The elimination of these microorganisms (bacteria, fungi, and viruses) occurs due to the generation of reactive oxygen species (ROS) in the semiconductor, even in the dark. ,, When interacting with propylene groups, different semiconductors such as Ag 2 XO 4 (X = W, Mo, and Cr) can increase their electronic density in the conduction band (CB). This transfer of electrons (e – ) from polypropylene increases the reducing character of the semiconductor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations